1972
DOI: 10.1002/bip.1972.360110608
|View full text |Cite
|
Sign up to set email alerts
|

Complementary DNA base interactions: Application of recently refined electrostatic interaction theory

Abstract: SynopsisElectrostatic interactions between the DNA bases in the Watson-Crick hydrogen bonding configuration are examined in both the molecular and the atomic multipole representations using three different methods of calculation: (a) CNDO wave functions and definitions of moments, (b) IEHT wave functions and division of two-center densities and (c) IHET wave functions with equally divided overlap densities. It is shown that the inclusion in the interaction series of terms at least as high as the quadrupole-qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Another approach that has been studied very extensively involves expressing V(7r) as a multipole expansion, written in terms of one or more centers (46)(47)(48). In a recent adaptation of this technique, designed to facilitate the treatment of large biological molecules, each overlap term in the electronic density function was replaced by a one-center expansion that went as far as the quadrupole terms (49).…”
Section: Methods Of Calculating the Electrostatic Potentialmentioning
confidence: 99%
“…Another approach that has been studied very extensively involves expressing V(7r) as a multipole expansion, written in terms of one or more centers (46)(47)(48). In a recent adaptation of this technique, designed to facilitate the treatment of large biological molecules, each overlap term in the electronic density function was replaced by a one-center expansion that went as far as the quadrupole terms (49).…”
Section: Methods Of Calculating the Electrostatic Potentialmentioning
confidence: 99%
“…The magnitude of this difference follows closely the trend set by the differences in angular minima as predicted by the SMMA and MMA electrostatic calculations. (8) -6.57 (7) t%I t E 1 (9) -12.1 (7) -7.02 (7) -6.78 (6) t K 1 See footnote a, Poly(dG).poly(dC)…”
Section: (4)mentioning
confidence: 98%
“…The present study, i.e., the inclusion of terms up to octopole interactions and the subsequent decomposition into inverse powers of R , gives a better insight into the convergence problem than the previous study [6]. With respect to electrostatic interactions it was observed that after some oscillations.…”
Section: Discussion and Resultsmentioning
confidence: 65%
“…By expanding both charge distributions in a Taylor series the interaction energies can be expressed as a series of multipole-multipole terms. We list below only those terms involving octopole interactions and refer the reader to other sources [5,6] for a description of terms in the series up to quadrupole-quadrupole interactions. Buckingham [ 121 describes the electrostatic octopole moment as (3) .…”
Section: Electrostatic Energymentioning
confidence: 99%
See 1 more Smart Citation